Donor-Derived Smoldering Multiple Myeloma following a Hematopoietic Cell Transplantation for AML. (20th February 2017) - Fakhri, Bita; Fiala, Mark; Slade, Michael; Westervelt, Peter; Ghobadi, Armin
Abstract : Posttransplant Lymphoproliferative Disorder (PTLD) is one of the most common malignancies complicating solid organ transplantation. In contrast, PTLD accounts for a minority of secondary cancers following allogeneic hematopoietic cell transplantation (HCT). Here we report on a 61-year-old woman who received an ABO-mismatched, HLA-matched unrelated donor hematopoietic cell transplantation from a presumably healthy donor for a diagnosis of acute myeloid leukemia (AML). Eighteen months following her transplant, she developed a monoclonal gammopathy. Bone marrow studies revealed 10% plasma cells, but the patient lacked clinical defining features of multiple myeloma (MM); thus a diagnosis of smoldering multiple myeloma (SMM) was established. Cytogenetic and molecular studies of the bone marrow confirmed the plasma cells were donor-derived. The donor lacks a diagnosis of monoclonal gammopathy of undetermined significance, SMM, or MM.